β-Adrenergic Receptor Stimulation and Alternans in the Border Zone of a Healed Infarct: An ex vivo Study and Computational Investigation of Arrhythmogenesis - Tomek, Jakub; Hao, Guoliang; Tomková, Markéta; Lewis, Andrew; Carr, Carolyn; Paterson, David J.; Rodriguez, Blanca; Bub, Gil; Herring, Neil (Frontiers in Physiology, 2019)
Background: Following myocardial infarction (MI), the myocardium is prone to calcium-driven alternans, which typically precedes ventricular tachycardia and fibrillation. MI is also associated with remodeling of the sympathetic innervation in the infarct border zone, although how this influences arrhythmogenesis is controversial. We hypothesize that the border zone is most vulnerable to alternans, that β-adrenergic receptor stimulation can suppresses this, and investigate the consequences in terms of arrhythmogenic mechanisms. Methods and Results: Anterior MI was induced in Sprague-Dawley rats (n = 8) and allowed to heal over 2 months. This resulted in scar formation, significant (p < 0.05) dilation of the left ventricle, and reduction in ejection fraction compared to sham operated rats (n = 4) on 7 T cardiac magnetic resonance imaging. Dual voltage/calcium optical mapping of post-MI Langendorff perfused hearts (using RH-237 and Rhod2) demonstrated that the border zone was significantly more prone to alternans than the surrounding myocardium at longer cycle lengths, predisposing to spatially heterogeneous alternans. β-Adrenergic receptor stimulation with norepinephrine (1 μmol/L) attenuated alternans by 60 [52–65]% [interquartile range] and this was reversed with metoprolol (10 μmol/L, p = 0.008). These results could be reproduced by computer modeling of the border zone based on our knowledge of β-adrenergic receptor signaling pathways and their influence on intracellular calcium handling and ion channels. Simulations also demonstrated that β-adrenergic receptor stimulation in this specific region reduced the formation of conduction block and the probability of premature ventricular activation propagation. Conclusion: While high levels of overall cardiac sympathetic drive are a negative prognostic indicator of mortality following MI and during heart failure, β-adrenergic receptor stimulation in the infarct border zone reduced spatially heterogeneous alternans, and prevented conduction block and propagation of extrasystoles. This may help explain recent clinical imaging studies using meta-iodobenzylguanidine (MIBG) and 11C-meta-hydroxyephedrine positron emission tomography (PET) which demonstrate that border zone denervation is strongly associated with a high risk of future arrhythmia.